USING ECLECTIC APPROACH TO IMPROVE THE STUDENTS’ READING COMPREHENSION - Wildhan Burhanuddin (Universitas Muhammadiyah Makassar, 2012)
The research aimed to find out the improvement of students’ reading comprehension in terms of finding main ideas and meaning of words at the students’ of SMPN 4 Libureng in the 2012/2013 academic year. This research used A Classroom Action Research that consisted two cycles. The sample of this research consisted of 22 students, those consisted of six women and twelve men.The researcher obtained the data by using reading test and observation sheet. The results of the student's reading test in cycle I and cycle II had significantly different scores. There was a better increase of gains by students at the end of the action in the second cycle. In the cycle, I, the students’ achievement of main ideas was 6,09, but after evaluation in cycle II, the students’ reading comprehension become 7,62.The other hand the students’ meaning of words was improved too from cycle I to cycle II, whereas in the students’ achievement of the meaning of words was 6,13, but after evaluation in cycle II, the students’ achievement becomes 7,74. From the findings indicated that there was the improvement in the students’ reading comprehension from cycle I to cycle II, whereas in cycle I students’ achievement reading comprehension was 23,81, but after evaluating in cycle II the students’ reading comprehension became 25,69. While the standard target achievement KKM 66. From these findings, the researcher made the conclusion that by using an eclectic approach could improve the students’ reading comprehension achievement. Key Word: Eclectic Approach, Improve, Reading Comprehension